ASSOCIATION OF DEPRESSIVE SYMPTOMS WITH TOTAL HEALTH CARE COSTS IN OLDER WOMEN. (11th November 2018) - Schousboe, J T; Vo, T; Langsetmo, L; Diem, S; Ensrud, K E
Abstract: Whether or not depressive symptoms predict total health care costs (THC) independent of both multimorbidity and functional impairment is unclear. In a prospective cohort of 2510 women (mean age 80.2 years) linked with Medicare claims, we estimated the association of mild depressive symptoms (Geriatric Depression Scale [GDS] score 2–5) and moderate-severe depressive symptoms (GDS score≥ 6) with subsequent annualized THC (2014$), before and after adjustment for multimorbidity and functional limitations. Compared to those with GDS score of 0 or 1, the cost ratio (95% CI) for those with mild and moderate-severe depressive symptoms, respectively, was 1.70 (1.45–1.99) and 1.89 (1.47–2.43) adjusted for age; 1.53 (1.30–1.79) and 1.55 (1.20–1.99) adjusted for age and multimorbidity; and 1.35 (1.14–1.59) and 1.27 (0.97–1.65) adjusted for age, multimorbidity, and impaired instrumental activities of daily living (IADLs). A substantial proportion of the association between depressive symptoms and higher THC is explained by multimorbidity and functional impairment.